ERP systems and corporate sustainability: The missing link of green accounting - Muhammad Nawawi; Wulan Retnowati; Tri Wahyudi; Edward Fazri (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2026)
This study examines how enterprise resource planning (ERP) systems influence corporate sustainability via green accounting, grounded in the Resource-Based View and accounting–sustainability integration theory. A structured survey of 137 professionals measured ERP, green accounting, and corporate sustainability constructs using three to four indicators each; data were analyzed using Partial Least Squares structural equation modeling (PLS-SEM). Results show that ERP adoption significantly enhances green accounting practices and corporate sustainability performance, with green accounting mediating ERP’s positive impact on sustainability outcomes. Theoretically, the study explicitly models the ERP–sustainability link through an accounting lens, enriching integrative frameworks that connect information systems and environmental outcomes. Practically, the findings suggest that managers should integrate ERP systems with robust environmental accounting modules to systematically collect, measure, and report environmental performance data, thereby transforming organizational practices toward sustainability and enabling more informed sustainability decision-making. Policy implications include aligning digital transformation efforts with sustainability reporting standards and regulatory frameworks to support broader environmental and economic goals.